1964
DOI: 10.1139/o64-043
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of Autoprothrombin C Activity With Antithrombin

Abstract: X concentrate of antithroinbin was made from bovine plasma. When examined with an analytical ultracentrifuge it was found to contain a main component and a sinall ail~ount of more rapidly sediinentating material. For the main component S j , , was 4.01 S. The antithroinbin concentrate destroyed the activity of purified autoprothrombin C, and most likely antithrombin and antiautoprothrombin C are one and the same substance. The antithrombin preparation was limited in its capacity to destroy autoprothrombin C ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1964
1964
2008
2008

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Both the esterolytic and coagulant activities of X, are slowly inhibited by soya bean trypsin inhibitor (70) and by plasma antithrombin (243). X, is rapidly inactivated by 2,3-dimercaptopropan-1-01 (39,128), and by DFP in the cold at 4 : l molar ratio of inhibitor to protein, inactivation being complete in 1 hr, as judged by the rate of hydrolysis of carbobenzoxy phenylalanine nitrophenol ester (128).…”
Section: Factor X and Activated Factor X (X)mentioning
confidence: 99%
“…Both the esterolytic and coagulant activities of X, are slowly inhibited by soya bean trypsin inhibitor (70) and by plasma antithrombin (243). X, is rapidly inactivated by 2,3-dimercaptopropan-1-01 (39,128), and by DFP in the cold at 4 : l molar ratio of inhibitor to protein, inactivation being complete in 1 hr, as judged by the rate of hydrolysis of carbobenzoxy phenylalanine nitrophenol ester (128).…”
Section: Factor X and Activated Factor X (X)mentioning
confidence: 99%
“…Autoprothrombin I I I is the precursor of autoprothrombin C and is not altered by antithrombin. With autoprothrombin I we found (14) that the activity disappears rapidly when placed in plasma or serum, or in solution with the antithrombin preparation of JIonkhouse and AIilojevic (15).…”
Section: Introductionmentioning
confidence: 93%
“…Several investigators have demonstrated the capacity of antithrombin to inhibit activated Factor X [3,50]. Rosenberg et al have examined the serine proteases of the intrinsic coagulation pathway in regard to their capacity to be antagonized by antithrombin and heparin [4,46].…”
Section: Intrinsic Coagulation Pathwaymentioning
confidence: 99%